2018
DOI: 10.1002/acn3.678
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neurofilament light correlates with CADASIL disease severity and survival

Abstract: ObjectiveTo validate whether serum Neurofilament Light‐chain (NfL) levels correlate with disease severity in CADASIL, and to determine whether serum NfL predicts disease progression and survival.MethodsFourty‐one (pre‐) manifest individuals with CADASIL causing NOTCH3 mutations and 22 healthy controls were recruited from CADASIL families. At baseline, MRI‐lesion load and clinical severity was determined and serum was stored. Disease progression was measured in 30/41 patients at 7‐year follow‐up, and survival o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…(10) Another study revealed that the serum NfL level not only correlated with cognition and functional disabilities at baseline but also predicted their longitudinal progression and overall survival. (11) Our study extended upon the previous findings by demonstrating that NfL can also be a useful marker for predicting stroke event in the future. Although neuroimaging lesion load or cognitive function were crucial prognostic factors in CADASIL, overt stroke event might engender greater threat to both patients and clinicians.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…(10) Another study revealed that the serum NfL level not only correlated with cognition and functional disabilities at baseline but also predicted their longitudinal progression and overall survival. (11) Our study extended upon the previous findings by demonstrating that NfL can also be a useful marker for predicting stroke event in the future. Although neuroimaging lesion load or cognitive function were crucial prognostic factors in CADASIL, overt stroke event might engender greater threat to both patients and clinicians.…”
Section: Discussionsupporting
confidence: 80%
“…(22) The initial manifestations or reasons for screening for NOTCH3 mutation in these patients were as follows, stroke in 52 patients, cognitive or gait deterioration in 7, headache or dizziness in 5, asymptomatic family members of known CADASIL patients in 3, and incidentally found marked leurkoaraiosis in 1. The patients' blood collected from different hospitals underwent genetic diagnosed centrally by combining p.R544C hot-spot mutation screening followed by sequencing of the most frequently mutated NOTCH3 exons (3,4,5,6,11,18) weighted imaging signal intensities through computed tomography (CT) or magnetic resonance imaging (MRI), respectively, that corresponded to the clinical presentations. ICH was defined as the sudden onset of focal neurological deficit with non-traumatic intraparenchymal hemorrhage observed on head CT or MRI scans.…”
Section: Participants and Clinical Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial manifestations or reasons for screening for NOTCH3 mutation in these patients were as follows: stroke in 52 patients, cognitive or gait deterioration in 7, headache or dizziness in 5, asymptomatic family members of known CADASIL patients in 3, and incidentally found marked leukoaraiosis in 1. The patients' blood collected from different hospitals underwent genetic diagnosed centrally by combining p.R544C hot-spot mutation screening followed by sequencing of the most frequently mutated NOTCH3 exons (3,4,5,6,11,18) if p.R544C was not detected. Sixty-five patients (96%) had NOTCH3 mutation on exon 11 p.R544C.…”
Section: Participants and Clinical Informationmentioning
confidence: 99%
“…Fluid biomarkers, especially blood-based, have the advantage of easy collection and repeat measurement over the relatively inconvenient neuroimaging tests. In CADASIL patients, the neurofilament light chain (NfL) blood level has been found to correlate with the clinical and neuroimaging burdens [10] and can predict their long-term disability and survival [11]. Fluid biomarkers are used for predicting the occurrences of IS and ICH in CADA-SIL patients; however, they have not been well studied.…”
Section: Introductionmentioning
confidence: 99%